Welfare assessment in rabbits raised for meat and laboratory purposes in enclosures with two floor types: Perforated plastic with holes versus slats. (February 2019) - Tillmann, K.; Windschnurer, I.; Gamper, J.; Hinney, B.; Rülicke, T.; Podesser, B.K.; Troxler, J.; Plasenzotti, R.
Abstract: Due to welfare concerns and legal restrictions in certain countries, alternatives to wire net floors must be developed in rabbit husbandries. Also, there is a difference in regulations in Europe for laboratory rabbits vs. rabbits bred and kept for meat production. While there are regulations concerning floor design of enclosures for rabbits bred for meat production in many European countries, the European Directive 2010/63 lacks regulations for rabbits used for scientific purposes. This study compares two floors, which meet the Austrian legal requirements for growing rabbits intended for consumption as well as the requirements for laboratory rabbits. The dual use of rabbits bred for meat production and applicable for scientific purposes would avoid the problem of surplus animals of specialized producers for laboratory rabbits. A noryl floor with 12 mm circular holes was compared to a 10 mm slatted plastic floor. Parameters were soiling of cages and animals, parasitic burden, clinical health, and losses using objective scoring. Soiling of cages and animals and coccidial oocytes were significantly higher on the floors with circular holes. Obvious signs of disease showed a non-significant trend to be more frequent in the group with circular holes. This was linked with significantly higher losses. In conclusion, our study clearly shows that the floor with circular hole design cannot be endorsed, although it meets legal requirements. The slatted floor type can be cautiously recommended; however, to assure animal welfare in laboratory rabbits, legal authorities in Europe should take on the responsibility of regulating floor design in this sector. Highlights: A floor for rabbits with circular 12 mm holes has been tested for the first time. A plastic floor with 10 mm slats was very clean and promising. The floor design with 12 mm holes is not recommendable. Study design was highly comparable since the floor design was the only difference.